Museo Colegial de Daroca - Mañas Ballestín, Fabián (Artigrama, 2014)
Resumen El Museo Colegial de Daroca se creó con bienes procedentes de las parroquias desaparecidas en 1902 y de la propia iglesia de Santa María de los Corporales. Se instaló en las antiguas Sacristía y Sala Capitular de ésta y se inauguró en 1939. A principios del siglo XXI se han añadido dos nuevos espacios; así en la actualidad consta de cuatro salas: una para la orfebrería, otra para ornamentos y dos para pintura. Tiene además una Sección II en un edificio propiedad del Ayuntamiento (P/ de Santo Domingo, 22) con abundantes tablas góticas. Tres excelentes colecciones —orfebrería, ornamentos y pintura— que precisan un espacio más adecuado. Abstract The Museum of the Collegiate Church of Daroca was founded with properties from churches that had disappeared in 1902, and also with properties from the Santa María de los Corporales church itself. It was placed at the Sacristy and its chapterhouse, and it was opened in 1939. At the beginning of the XXI century two new areas were added and currently the museum consists of four rooms: one for precious metal work, another one for ornaments, and two for paintings. It has additional space in a building that belongs to the city council (Section II, Santo Domingo square, 22) that contains a variety of Gothic panel paintings. These three excellent collections (precious metal work, ornaments and paintings) deserve a more suitable space. Key words Museum, Daroca, precious metal work, ornament, painting, Gothic, crosses, reliquary, images.